1998
DOI: 10.1093/protein/11.12.1181
|View full text |Cite
|
Sign up to set email alerts
|

Domain swapping in G-protein coupled receptor dimers

Abstract: Computer simulations were performed on models of the beta2-adrenergic receptor dimer, including 5,6-domain swapped dimers which have been proposed as the active, high affinity form (here the dimer interface lies between helices 5 and 6). The calculations suggest that the domain swapped dimer is a high energy structure in both the apo dimer and in the presence of propranolol. In the presence of agonist the energy of the domain swapped dimer is significantly lowered. Analysis of the dimer structure suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 3 publications
4
83
0
2
Order By: Relevance
“…Data from microscopy, covalent cross-linking, and x-ray crystallography experiments have revealed that cell surface receptors from many structural classes assemble into multi-receptor complexes; these include some heptahelical G-protein coupled receptors (GPCRs), [36][37][38] methyl-accepting chemotaxis proteins (MCPs), [39] gated ion channels, [40] receptor protein tyrosine kinases (RPTKs), [41,42] and multichain immune recognition receptors (MIRRs). [22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands.…”
Section: Signaling Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from microscopy, covalent cross-linking, and x-ray crystallography experiments have revealed that cell surface receptors from many structural classes assemble into multi-receptor complexes; these include some heptahelical G-protein coupled receptors (GPCRs), [36][37][38] methyl-accepting chemotaxis proteins (MCPs), [39] gated ion channels, [40] receptor protein tyrosine kinases (RPTKs), [41,42] and multichain immune recognition receptors (MIRRs). [22,33,35,[43][44][45] The size of these ensembles varies: Some complexes are composed of two receptors while others contain thousands.…”
Section: Signaling Complexesmentioning
confidence: 99%
“…[49] For example, helix-mediated multimerization is proposed to mediate the dimerization and oligomerization of GPCRs (Figure 2). [38,50,51] Evidence for the functional importance of these interactions is suggested by engineering disrupting mutations in the proposed contact sites or by adding isolated transmembrane helices to GPCRs. [37,52,53] Although their effects on receptor oligomerization are not yet well-established, these manipulations modulate signaling; presumably, they disrupt receptor-receptor contacts.…”
Section: Signaling Complexesmentioning
confidence: 99%
“…Fig. 4 shows one of the proposed structural models for GPCR receptor dimers, 5,6-domain swapped dimers (Gouldson et al ., 1998). Each transmembrane alpha helix is represented as a circle.…”
Section: Hgnrhr-2v Knocked Downmentioning
confidence: 99%
“…However, a growing body of functional and biochemical evidence suggests that they may exist as homo-or heterodimers. The functional evidence is based largely on positive and negative effects that dominant receptor mutants have on wild-type receptor function and on the observation that coexpression of two defective receptors can restore activity (1)(2)(3)(4)(5)(6). More recently, coexpression of the type-2b ␄-aminobutyric acid receptor GABAb-R2 was found to be essential for the cell surface expression and the function of the GABAb-R1 subtype (7)(8)(9), suggesting that heterodimerization between the two receptor molecules is required for function.…”
mentioning
confidence: 99%